Memorial parks for Philippine towns a study of cemeteries as open space - Duenas, Nathanael John G. 1947- (1975)
The study is based on the philosophy of life-after death and that treasure his burial as he treasures his life on Earth. The perpetuation of this philosophy can be shown architecturally in its community context in the form of the memorial park that has been designed and planned in the true meaning of open space. The discussion evolves mainly from the existing cemetery and an open space in most, if not all, land use maps and the contrasting differences between a cemetery and an open space. This study dwells on how this classification as open space can be achieved by the cemetery through the application of the memorial park concept, and why the memorial park concept was chosen among other alternatives. A look into the existing cemeteries and memorial parks in relation to the urban development of Metropolitan Manila and the municipalities and towns in several provinces and cities, i.e., the cities of Lipa, Baguio, San Jose, Bacolod and Iloilo, Angeles, Pampanga; Rosales, Pangasinan; has given a clear insight of the pattern of cemetery planning in the Philippines; the relationship of the economic, social, political and cultural aspects in laying out these cemeteries and memorial parks, and the possible consequences arising thereof in terms of art and culture, architecture and the ecosystem. A feasibility study for a hyphothetical one-hectare memorial park is presented for the purpose of implementing the memorial concept into the various levels of Philippine towns and its realtions to different site locations. The thesis also explores the possibility of the local government and/or the church to develop and convert old cemetery properties into memeorial parks with consequent benefits to the public and community in the form of recreational facilities, an enhancement of community life and the upliftment of culture. Generalization in terms of cultural significance take into consideration the majority of Pilipino Christians, specially the Roman Catholics. The approach undertaken in this study was based on nature planning as emphasized by Ian McHarg's book, "Design with Nature", in order to bring about a totally different architecture oriented to ecology and ecological design and an analysis grasp of the present cemetery situation in the Philippines and its role in the community as open space
Thesis (Master of Architecture : Community Architecture)--University of the Philippines, Diliman.
Keywords: Cemeteries -- Landscape architecture; Memerial parks (Cemeteries).